City as an urban social diversity: A case study of Rukun Tetangga in Kuala Lumpur and Selangor - Dora, Mohd Taib; Abdul Majid, Izaidin; Raja Abd Rahman, Raja Roslan; Kudus, Norliah; Mat, Zawiah; Othman @ Abdul Halip, Noor Maslian (2007)
The purpose of this research is to examine the level of knowledge, perception and acceptance among the public towards programs organized by Rukun Tetangga (RT). The programs organized include social, educational and recreational activities. Activities related to health and environment, welfare, art and culture, economy and public safety are also carried out. This research looks at the correlation analysis between demographic variables of the respondent with the level of knowledge, perception and public acceptance towards the program organized. In brief, this research tries to answer the question of how far is the effectiveness of RT in organizing activities to promote unity among our community. This is considered as beneficial development in order to identify the RT's direction in the future. The research is done in a few districts in Selangor and Federal Territory of Kuala Lumpur. The selected areas are chosen due to the existence of diversified characteristics of the community that is relevant to the research needs. The characteristics include the aspect of different races and the distribution of location as they are thought to be a threat towards the solidarity among the main races. Moreover, the location is identified because it is the highest in population in the country. The research shows that the knowledge level, perception and public acceptance toward the programs organized by RT are generally high. This result can be used as an indicator that RT is a success entity in all situations. It has also increased harmony and contributed to national integration among Malaysians.